Heterosis and combining ability of seed physiological quality traits of single cross vs. three-way sorghum hybrids - Marisol Galicia-Juárez; Leopoldo Ernesto Mendoza-Onofre; Víctor Arturo González-Hernández; María Eugenia Cisneros-López; Ignacio Benítez-Riquelme; Leobigildo Córdova-Téllez (Acta Scientiarum. Agronomy, 2017)
The aim of this research was to compare genetic parameters for traits related with seed germination and seedling vigour of single cross (SCH) vs. three-way (TWH) sorghum hybrids. The study was conducted in a sand bed under a greenhouse; 67 genotypes (four pairs of A- and B- lines, four R- lines, 13 SCH and 42 TWH) were allocated in a randomized complete blocks experimental design with three replications. Statistical analysis included ANOVA’s and Student “t” tests, while Tukey test (p £ 0.05) was applied for mean comparisons. The R-lines showed better physiological seed quality attributes than the A- and B- lines. The seed quality and heterosis values of SCH vs. that of TWH did not show significant differences (p > 0.05) for any variable; however, heterobeltiosis of SCH was higher than that of TWY for normal seedlings, dry weight of plumule and seedling emergence rate. The A2- line and R14 restorer line showed the highest GCA values in both types of hybrids. No differences (p ≤ 0.05) were found between maternal and paternal effects of the A- and B- lines involved in the male sterile cross (female parent) of the TWH, except for plumule length in Line 5.